Analisis Masalah Guru Profesional Berdasarkan Kompetensi Pedagogik terhadap Kinerja Guru Pasca Diklat Pendidikan Profesi Guru di Sekolah Dasar : Literatur Review - Fuad Hasim; Tri Joko Raharjo; Harianingsih Harianingsih (PT. Pusmedia Group Indonesia, 2025)
The background of this research focuses on the importance of the quality of education which is influenced by the ability of teachers to design and implement effective learning. This study aims to analyze the pedagogic competence of teachers and the challenges faced in their application after participating in the Teacher Professional Education (PPG) program in elementary schools. The method used is a literature review by reviewing various scientific journals from 2016 to 2024 related to pedagogic competence and teacher performance. The database information used for this article is Google Scholar. Data were obtained using the keywords